Unilateral proptosis: an unusual presentation of prostatic carcinoma. (27th May 2013) - Pouncey, Anna Louise; Fox, Thomas Peter; Bryant, Catherine Anne
Abstract : A 68-year-old man presented acutely with periorbital pain and proptosis of the right eye, on a background of generalised pain and weight loss. Imaging showed bilateral signal abnormalities in the basal skull extending into the extraconal orbits with compression of the right optic nerve. His medical history revealed symptoms in keeping with benign prostatic hypertrophy. However, the prostate was irregular on rectal examination and prostate-specific antigen was markedly raised at 1880 ng/dl. A provisional diagnosis of metastatic prostatic carcinoma was made based on the clinical and radiological picture. This was later confirmed to be metastatic adenocarcinoma through means of tissue diagnosis.